Education Research: Online Alzheimer education for high school and college students. (20th October 2020) - Saif, Nabeel; Niotis, Kellyann; Dominguez, Moises; Hodes, John F.; Woodbury, Michael; Amini, Yasmin; Sadek, George; Scheyer, Olivia; Caesar, Emily; Hristov, Hollie; Knowlton, Newman; Lee, Paige; et al.
Abstract : Objective: Alzheimer disease (AD) risk factors are present throughout the lifespan. This randomized controlled trial evaluated the effectiveness of various online education strategies concerning AD risk reduction and brain health in younger populations. Method: High school and college students were recruited via social media (Facebook and Instagram) to join AlzU.org, an evidence-based education portal, and were randomized to 1 of 4 courses: highly interactive webinar lessons narrated by actor Seth Rogen (celebrity webinar) or a physician (doctor webinar), minimally interactive video lessons with Seth Rogen (celebrity video), or minimally interactive video lessons (control). Surveys were administered at baseline and postcourse. The primary outcome was change in knowledge of AD risk reduction assessed by pre vs post lesson quiz scores. Secondary outcomes included change in awareness of AD research, hopefulness about AD, interest in pursuing health care, willingness to volunteer, and likelihood of recommending AlzU.org . Result: A total of 721 participants joined. A total of 281 (38.9%) completed the course. Among college students, quiz score improvements were greater in celebrity webinar and celebrity video vs doctor webinar and control. Among high school students, no differences were found in quiz scores. In both groups, celebrity webinar, celebrity video, and doctor webinar resulted in greater improvements in awareness that nutrition and exercise may reduce AD risk vs controls. Among college students, celebrity webinar and celebrity video group participants felt more hopeful about the future of AD and more likely to recommend AlzU.org vs doctor webinar and control participants. Among college students, celebrity webinar, celebrity video, and doctor webinar participants were more willing to volunteer for AD causes and pursue health care careers vs controls. Conclusion: Online education involving a celebrity may be an effective strategy for educating college students about AD risk reduction strategies. Further studies are warranted in high school students.